The critical role of ants in the extensive dispersal of Acacia seeds revealed by genetic parentage assignment - Pascov, C.; Nevill, Paul; Elliott, C.; Majer, Jonathan; Anthony, J.; Krauss, S. (Springer Verlag, 2015)
Ants are prominent seed dispersal agents in many ecosystems, and dispersal distances are small in comparison with vertebrate dispersal agents. However, the distance and distribution of ant-mediated dispersal in arid/semi-arid environments remains poorly explored. We used microsatellite markers and parentage assignment to quantify the distance and distribution of dispersed seeds of Acacia karina, retrieved from the middens of Iridomyrmex agilis and Melophorus turneri perthensis. From parentage assignment, we could not distinguish the maternal from each parent pair assigned to each seed, so we applied two approaches to estimate dispersal distances, one conservative (CONS), where the parent closest to the ant midden was considered to be maternal, and the second where both parents were deemed equally likely (EL) to be maternal, and used both distances. Parentage was assigned to 124 seeds from eight middens. Maximum seed dispersal distances detected were 417 m (CONS) and 423 m (EL), more than double the estimated global maximum. Mean seed dispersal distances of 40 m (±5.8 SE) (CONS) and 79 m (±6.4 SE) (EL) exceeded the published global average of 2.24 m (±7.19 SD) by at least one order of magnitude. For both approaches and both ant species, seed dispersal was predominantly (44–84 % of all seeds) within 50 m from the maternal source, with fewer dispersal events at longer distances. Ants in this semi-arid environment have demonstrated a greater capacity to disperse seeds than estimated elsewhere, which highlights their important role in this system, and suggests significant novel ecological and evolutionary consequences for myrmecochorous species in arid/semi-arid Australia.